Occupational risk assessment of the royal Malaysia police cid personnel - Razali, Sabardin (2001)
The detectives are the plain clothed lower ranking officers who are attached to various sections and units in the CID. They are the group of officers who will carry out the detailed instructions given by the officers. Their job includes the execution of arrest, surveillance. Escort, search, investigation and raids. The aim of the study is to assess the occupational risks faced by the CID detectives of the Royal Malaysia Police in the performance of their job. There has not been such study carried out before. However, there were some similar studies published by police research units abroad. Detectives from Kuala Lumpur Contingent were taken as sample to represent the detectives in the whole country. Questionnaires were issued to them to seek information about the occupational risks they encountered. The questionnaire focused on areas of personal background, courses and training, employment and regulations, risks and equipments. One hundred and fifty-five questionnaires were distributed. However, only one hundred and thirteen questionnaires were good for analysis. The tools used were the SAS and Excel system. Results were presented in demographic profiles, for areas where statistical analysis were found inapplicable. From Pearson correlation analysis, the factors of unit, frequency of job, personal protective and rank were found to be significantly correlated with risks. However, courses and training factor were found not to be significantly with risk factor. In another approach, regression analysis was used. Risk was used dependent factor, while unit, frequency of job, personal protective equipment and rank were taken as independent factors. The relationship of the factors was expressed as a model. In this study, the figure of R² (63%) shows that there are some other factors contributing to risk assessment. Further study is recommended to look for a higher consistency model for risk assessment is this area of study.